From Folksmentshn to Creative Individuals: Klezmer Transmission in the Twenty-First Century - Scherbenske, Amanda L. (MUSICultures, 2012)
During the mid-1970s, American Jewish musicians active in a variety of musical genres took an interest in eastern European Jewish roots music. This efflorescent enthusiasm for it came to be known as the klezmer revival. In 1985 Henry Sapoznik founded the first klezmer institute. Since then, numerous institutes have sprung up across North America and Europe. Despite their emergence as one of the most popular formats for the enactment of community and for learning Yiddish cultural expressions, klezmer transmission has rarely been the focus of scholarly attention. This article contends that revivalists and subsequent generations have created an ethos for a music culture through transmission processes, demonstrating veneration both for an “authentic” Jewish cultural heritage and for individualized cultural expressions.